الأساليب الطلبية في سورة الكهف- دراسة نحوية تحليلية إحصائية - صــالح سـعـاد أحـمد مـحـمـد (Sharwes Scientific Journal, 2024)
The aim of the study is to explain the importance of application methods, their tools, and their linguistic dimensions, and to clarify their features in Surat Al-Kahf, and in serving the Qur’anic text. In this study, the analytical-inductive-statistical approach, was used using all the sources available. This research consists of an introduction to Surah Al-Kahf, its characteristics, and its educational goal and the manifestations of the imperative construction and its types, which are: the question, the command, the prohibition, the call, and the wish, then a conclusion in which I mentioned the most important results of the research, which are: 1_There is a close relationship between grammar and rhetoric, which becomes clear through their connection to the other, which appears clearly in Surat Al-Kahf. 2_One of the most frequently mentioned verbal styles in Surat Al-Kahf is the interrogative style, which appears with seven devices. 3_ It is followed by the imperative form, which appears in two forms: the imperative verb in the form (I do)، and the present tense of the imperative verb in the form (to do). 4_ The style of the call that was received is omitted, and with the article (ya). 5_The style of prohibition that is stated in the present tense form coupled with no definitive prohibition. 6_The method of wishing, which is stated in one form: I wish I had.